A short review of memory research - Igor Areh (Psihološka Obzorja, 2004)
Scientific research on memory began at the end of 19th century with studies of semantic and/or long term memory. In most cases memory was interpreted as a storehouse for various data and the quality of the storehouse was usually defined by a quantity of recalled data. The research work was concentrated on specificity of the connection between memory and learning. At that time few authors developed theories which were rare, uncommon and before their time (e.g.: Bartlett, Ribot, Freud). Even after 20th century, when behavioural stimulus-response approach began to dominate, the measure of memory quality was still the quantity of memory recall. In the 1960th the rise of cognitive psychology began, the computer metaphor was born and finally the behavioural comprehension of cognitive system was surpassed. Cognitive system was understood as a computer-like interface between an organism and environment. In recent years the computer metaphor is no longer dominant. New and efficient concepts are moving forward. Quantity of data recall, as the measure of memory quality, is not so important any more – attention is focused on accuracy of memory recall.